2020
DOI: 10.7759/cureus.8431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anemia and the Goal of Optimal HbA1c Control in Diabetes and Non-Diabetes

Abstract: Hemoglobin A1c (HbA1c) is the gold standard for the diagnosis of diabetes; however, many clinical conditions affect the HbA1c level, including anemia. And, the most common causes of anemia worldwide include iron deficiency anemia (IDA). We performed a systematic search using different combinations of MeSH words from the electronic database for the last 10 years (2011 to 2020). Articles included in the study were observational, randomized controlled trial (RCT), and review/systematic review. A total of 18 artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Hence, monitoring of HbA1c along with iron deficiency anemia patients should be taken with caution. This finding has come to the same conclusion as an interventional study which included a hundred and twenty people by Kalairajan et al in 2019 [16]. The study concluded that HbA1c levels have decreased in iron deficiency anaemia patients.…”
Section: Hba1csupporting
confidence: 70%
“…Hence, monitoring of HbA1c along with iron deficiency anemia patients should be taken with caution. This finding has come to the same conclusion as an interventional study which included a hundred and twenty people by Kalairajan et al in 2019 [16]. The study concluded that HbA1c levels have decreased in iron deficiency anaemia patients.…”
Section: Hba1csupporting
confidence: 70%
“…Both diabetes mellitus (DM) and anemia are common in the elderly population, and both are associated with the severity of the course of many comorbidities (especially cardiovascular diseases) and an increase in the risk of death [1][2][3][4][5]. In 2019, 463 million people worldwide were diagnosed with diabetes and approximately 20% of them were in their 60s [6].…”
Section: Introductionmentioning
confidence: 99%
“…107 Table 2 shows the relationship between the average CGM glucose and the GMI values. 107 Importantly, the GMI value is less influenced by conditions, such as anemia, 102 altered red blood cell lifetime, 100 hemoglobinopathies, 99 iron deficiency, 108 and pregnancy, 103 which can confound A1C measurements. 109 However, because measured A1C results are altered by these conditions, the correlation of the GMI and mean glucose can vary.…”
Section: Recommendations With Evidence Basementioning
confidence: 99%